Design and Analysis of 2oo3 Static Voter for SMT function in an Adjustable Speed Electrical Power Drive System - Summatta, C.; Deeon, S. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2019)
In fail-safe systems, a 2-out-of-3 voter is responsible for processing the monitoring of failures of the sensor unit in the system. When a failure has occurred and the outputs directly drive the vital units, there may be some injuries, loss or damages, such as in a nuclear reactor shutdown, railway signalling systems, industrial compression systems, or electric motor drive systems. This paper presents an innovatively designed and developed 2-out-of-3 static voter that detects the signal with a window comparator circuit related to the safety system for the detection of false signals. The voting function is mainly one diode and four optoelectronic switches, which reduces the number of devices, resulting in a lower failure rate. Failure of the voter is detected and corrected by the window comparator with digital switching levels, which is a very simple circuit that is used with low voltage and fast varying input. Furthermore, the analysis of the performance was conducted for IEC 61800-5-2 in an adjustable speed electrical power drive system, with the simulation of the failure rate of electronic equipment, mean time to failure, failure mode and effects analysis (FMEA), and the experimental circuit.